Separation of Empagliflozin and its Impurities by Validated Stability Indicating HPLC Method and LC-MS Characterization of Oxidative Degradation Product - Bhawani, Sunkara; Kumar, T.N.V. Ganesh (Asian Journal of Chemistry, 2023)
The HPLC assay strategy for two impurities (EPN-R-ISO impurity and the EPN-Diol impurity) which are related to empagliflozin synthesis was designed and verified for the reliable measurement of EPN-R-ISO and EPN-Diol impurities in empagliflozin bulk APIs. The chromatographical EPN-R-ISO and the EPN-Diol impurities analysis was done on Discovery C18 stationery column with isocratic type mobile phase exploited was potassium dihydrogenphosphate (0.01 M, pH calibrated to 2.0 by phosphoric acid) and acetonitrile in 70%:30% v/v ratio and injected at a flow measure of 1.0 mL/min. The degradation of empagliflozin under stressful conditions such as acid generated hydrolysis, base generated hydrolysis, peroxide generated oxidation, thermal generated degradation and UV generated hydrolysis was also included. The method established was verified for precision (0.0837% RSD for EPN-R-ISO; 0.1831% RSD for EPN-Diol), sensitivity (LOD: 0.030262 ppm EPN-R-ISO concentration, 0.031873 ppm EPN-Diol concentration; LOQ: 0.092621 ppm EPN-R-ISO concentration, 0.09755 ppm EPN-Diol concentration), linearity (0.1 ppm to 90.0 ppm concentration of both EPN-R-ISO and EPN-Diol) and accuracy (95.07% to 96.27% EPN-R-ISO recovery; 97.72% to 100.03% EPN-Diol recovery).